Pembekalan Peningkatan Kinerja UMKM Melalui Orientasi Keuangan dan Penjualan (UMKM Makanan Ringan Jalan Merdeka Pontianak) - Louw, Febriana; Indah, Nopiani; Santika, Dewi; Hiong, Lauw Sun (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
The number of MSMEs in Indonesia continues to increase every year. MSMEs have an important role in Indonesia's national development. The presence of these businesses helps to absorb labor, so that people can have an income. The large number of food and beverage businesses is because food and beverage businesses are closely related to people's daily lives, can be built with little capital, and require little labor. Business people need to see changing market trends and know what consumers want in order to create the right products. Financial orientation is an activity that focuses on managing financial conditions related to using cash and generating cash returns. Meanwhile, sales orientation is focused on selling products, providing an overview of the product to customers, offering products based on company stock, and producing not based on customer needs. With the provision of financial and sales orientation, it is hoped that snack food MSMEs can improve their business results management methods and design better sales strategies so that they can improve their business performance.